Factors Affecting Profitability of Nepalese Non-Life Insurance Companies - Hamal, Janga Bahadur (Journal of Nepalese Business Studies, 2020)
The study examines the impacts of liquidity ratio, leverage ratio, firm size, age of the firm and total debt on the profitability of non-life insurance companies in Nepal. The dependent variable in the study is the return on asset (ROA), which is used as a measure of profitability. The study is based on secondary data of nine non-life insurance companies studied over a period of ten years, from 2066/67 to 2075/76. The data were collected from the financial statements published annually by the selected non-life insurance companies. Descriptive statistics, correlational analysis and regression models have been employed in order to test the impacts as well as the significance of the selected independent variables on ROA. The study concludes that the profitability of Nepalese non-life insurance companies increases with the increase in liquidity but decreases with the increase in leverage. However, the study establishes the insignificant relationship of firm size, firm age and total debt with profitability for the sector. The study thus suggests that non-life insurance companies should focus on the proper management of capabilities to pay liabilities to enhance profitability and also try to maintain a smaller value of leverage ratio to handle the above-average losses.